Pengembangan dan Strategi Perlindungan Hukum atas Ekspresi Budaya Tradisional Di Kabupaten Lebak - Sulasno Sulasno; Wahyuddin Wahyuddin; Fitria Agustin (Ajudikasi : Jurnal Ilmu Hukum, 2021)
This Research is aimed at knowing the development and strategy of law protection against Traditional Cultural Expressions in the Lebak district. In this Research, theoretically useful for society’s undergrad students. Practices are useful to both art and cultural users,of the Education and Cultural Services,of the Tourism service and associated agencies. But currently researchers have not found any particular protection against Traditional Cultural Expressions in the Lebak district. The expressions of traditional culture is a trademark of a people worthy of protection. The provision intended to avoid the actions of foreigners who might damage the cultural values. Since the role of the government to provide protection was necessary, it was necessary to bring out specific law. The qualitative work involves an empirical normative study method of law research by digging into the regulatory regulations. In addition to that researchers do retrieve direct data from communities.